Disability certification for parkinson's disease in India: Challenges and the way forward - M Arun; Priya Treesa Thomas; Nitish L Kamble; Ravi Yadav; Pramod Kumar Pal (Wolters Kluwer Medknow Publications, 2023)
Disability certification is mandatory for people with Parkinson's disease to avail any schemes and benefits in India. The process of certification of the extent of disability in a complex disorder like Parkinson's needs to be made less cumbersome and streamlined to ensure that people for whom the benefits are meant are able to avail them.